The Pathfinders Society. The curse of the crystal cavern - Sedita, Francesco; Seraydarian, Prescott (Viking, 2021)
Using famous adventurer Henry Merriweather's journal as a guide, Kyle, Beth, Harry, Victoria, and Nate follow a secret stairway into underground passages beneath Windrose in search of the treasure he left behind, and receive mysterious visions from the past and learn of a secret society.